Removal of Cephalexin from Aqueous Solutions by Activated Carbon Adsorbent - Maryam Hemmati; Arezoo Ghaemi; Haman Tavakkoli (Mashhad University of Medical Sciences, 2019)
Introduction: Environmental problems caused by arrival of antibiotics in water resources due to toxicity and lasting effects are a serious threat. This study has been aimed to evaluate the efficiency of granular activated carbon as adsorbent for the removal of Cephalexin from aqueous solutions. Materials and Methods: This study was performed at laboratory scale and batch system. The influence of process variables such as pH of solution, adsorbent dosage, initial Cephalexin concentration and contact time were Investigated. Equilibrium study data were modeled using Langmuir, Freundlich and Temkin, moreover, kinetic studies were done by models of pseudo first order and pseudo second order. Findings: This research found that the Cephalexin adsorption efficiency decreased by increasing pH from 2 to 14, so that after 3 hours, the adsorption efficiency at the 20 mg.L-1 initial Cephalexin concentration and 0.2 g adsorbent, obtained 92.812%, 90.525% and 41.394% at pH 2, 3.5 and 14, respectively. The adsorption of Cephalexin was compatible with Langmuir isotherm and pseudo second order kinetic. Discussion and Conclusions: The present study showed that the granular activated carbon has high potential for adsorption and separation of Cephalexin and such pollutants from aqueous solutions, in addition to features like simple and rapid separation.